Predatory Inclusion in the Market for Rental Housing: A Multicity Empirical Test - Max Besbris; John Kuk; Ann Owens; Ariela Schachter (Socius, 2022)
Using a unique data set of millions of advertisements for rental housing and data on the geographic distribution of housing voucher holders, we examine the limits of housing market policies that rely on private-market landlords to meet public needs. We find that although advertised affordable housing is more prevalent in some zip codes than others, voucher households are more geographically clustered than affordable housing. Moreover, voucher holders are overly concentrated in “lower opportunity” zip codes, those with fewer resources for children’s well-being, despite the advertisement of affordable housing in higher opportunity neighborhoods. Using text-analysis techniques, we identify advertisements that explicitly accept or reject voucher holders and find that ads seeking voucher-holding tenants are overrepresented in lower opportunity neighborhoods. We evaluate the significance of these findings for theories of predatory inclusion.